CircMAPK1 induces cell pyroptosis in sepsis-induced lung injury by mediating KDM2B mRNA decay to epigenetically regulate WNK1 - Min Li; Hanjing Lu; Chujun Ruan; Qiao Ke; Longhui Hu; Zhao Li; Xiaoran Liu (Molecular Medicine, 2024)
Abstract Background Macrophage pyroptosis is a pivotal inflammatory mechanism in sepsis-induced lung injury, however, the underlying mechanisms remain inadequately elucidated. Methods Lipopolysaccharides (LPS)/adenosine triphosphate (ATP)-stimulated macrophages and cecal ligation and puncture (CLP)-induced mouse model for sepsis were established. The levels of key molecules were examined by qRT-PCR, Western blotting, immunohistochemistry (IHC) and ELISA assay. The subcellular localization of circMAPK1 was detected by RNA fluorescence in situ hybridization (FISH). Cell viability, LDH release and caspase-1 activity were monitored by CCK-8, LDH assays, and flow cytometry. The bindings between KDM2B/H3K36me2 and WNK1 promoter was detected by chromatin immunoprecipitation (ChIP) assay and luciferase assay, and associations among circMAPK1, UPF1 and KDM2B mRNA were assessed by RNA pull-down or RNA immunoprecipitation (RIP) assays. The pathological injury of lung tissues was evaluated by lung wet/dry weight ratio and hematoxylin and eosin (H&E) staining. Results CircMAPK1 was elevated in patients with septic lung injury. Knockdown of circMAPK1 protected against LPS/ATP-impaired cell viability and macrophage pyroptosis via WNK1/NLRP3 axis. Mechanistically, loss of circMAPK1 enhanced the association between KDM2B and WNK1 promoter to promote the demethylation of WNK1 and increase its expression. CircMAPK1 facilitated KDM2B mRNA decay by recruiting UPF1. Functional experiments showed that silencing of KDM2B or WNK1 counteracted circMAPK1 knockdown-suppressed macrophage pyroptosis. In addition, silencing of circMAPK1 alleviated CLP-induced lung injury in mice via KDM2B/WNK1/NLRP3 axis. Conclusion CircMAPK1 exacerbates sepsis-induced lung injury by destabilizing KDM2B mRNA to suppress WNK1 expression, thus facilitating NLRP3-driven macrophage pyroptosis.